2003
DOI: 10.1149/1.1545462
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Magnetic Characterization of Electrodeposited, High Moment FeCoNi Films

Abstract: We investigated the electrochemical deposition process of Fe-Co-Ni alloys from sulfate electrolytes containing no organic additives and the structural, magnetic, and electrical properties of the resulting films. The effect of pH and Co and Fe concentrations in the electrolyte on alloy composition is examined. The pH of the solutions is kept at 2.8 to minimize the incorporation of nonmagnetic matter. With increasing Ni content, a transition of the film structure from body-centered cubic ͑bcc͒ to face-centered c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
62
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 39 publications
8
62
0
Order By: Relevance
“…It is to be noted that the pH also differs for the two baths used in the above comparison. It is also known [41][42][43] that the mole fraction of Fe and Co in Ni-Co-Fe deposits decrases with the increase in pH if pH >2.8. However, we can exclude that the effect of the pH is dominant in the composition change observed since the initial Fe mole fraction is nearly the same.…”
Section: Composition Depth Profile Of Dc-plated Ternary Ni-co-fe Almentioning
confidence: 99%
See 1 more Smart Citation
“…It is to be noted that the pH also differs for the two baths used in the above comparison. It is also known [41][42][43] that the mole fraction of Fe and Co in Ni-Co-Fe deposits decrases with the increase in pH if pH >2.8. However, we can exclude that the effect of the pH is dominant in the composition change observed since the initial Fe mole fraction is nearly the same.…”
Section: Composition Depth Profile Of Dc-plated Ternary Ni-co-fe Almentioning
confidence: 99%
“…This is why TEM was applied for Ni-Co-Fe samples deposited with analogous conditions than those studied with SNMS reverse depth profiling. In former reports describing a TEM study of Ni-Co-Fe samples [39,41,[44][45][46], the near-substrate composition gradient shownin the previous chapter was not mentioned.…”
Section: Tem Analysis Of Dc-plated Ni-co-fe Alloys Obtained From a mentioning
confidence: 99%
“…The crystal structure changing from FCC to FCC+BCC does not seem to induce any measurable change in the magnetic moment of the CoFeNi films (~1.8 T, Figure 7). Previously reported results for CoFeNi films deposited with the direct current (DC) method indicate that desirable region for soft CoFeNi films is the one where either both crystal phases coexist or the alloy composition is on the boundary of the two-phase region 2,3,7,9,33 . Similarly, our data indicate that in the case of the pulse deposited CoFeNi films, the magnetic softness is promoted with the appearance of BCC phase ( Figure 6 -Figure 8).…”
Section: X-ray Diffraction Measurementsmentioning
confidence: 99%
“…Besides a commonly seen action of leveling and brightening of the deposit, the benefit of additives in plating bath was usually attributed to improvement in the grain size and the crystal structure of the deposit 2,3 , stress reduction 4 , suppression of hydrogen evolution 4 , and improved corrosion resistance of the deposit 5 . Recently, it was demonstrated that the appropriate choice of the additives and bath chemistry could substantially improve the magnetic properties of the CoFeNi films 2,6,7,8,9 . Magnetically very soft CoFeNi alloys with coercivity less than 2 Oe and high magnetic moment (>1.8T) were produced leading to substantial breakthrough in electrodeposited magnetic head core materials used for high density magnetic recording 2,7,9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation